Use of antigenic composition to differentiate among Rhizoctonia solani isolates from flax - Hussein, EM; Aly, AA; Ghel-Hawary, Ola; Mohamed, Heba I; Mosa, AA; Mostafa, MH (Bangladesh Journal of Botany, 2018)
Rhizoctonia solani is an plant pathogenic fungus with a wide host range and worldwide distribution. Double diffusion technique was used to differentiate among Rhizoctonia solani isolates from flax. In this technique, antisera of isolate 23 (AG-2) and isolate 24 (AG-4) reacted against antigens of 24 isolates belonging to AG-2 and Ag-4. The antiserum of isolate 23 (AG-2) was insensitive to differentiate among the isolates of AG-2, while it was highly sensitive to differentiate among some isolates of AG-4. The antiserum of isolate 24 (AG-4) was highly sensitive as a serotaxonomic tool to differentiate among AG-2 and AG-4, while it was of limited value in differentiating among isolates of within each AG.